An Introduction to Modern Economics / Fourth Edition - Hardwick Philip; Khan Bahadur; Langmead John (Longman, 1994)
A thorough revision of a classic, best-selling text - Hardwick, Khan and Langmead's Introduction to Modern Economics. Preface, Acknowledgements, The Nature and Scope of Economics, Production, Demand, Utility and Demand, Supply, Equilibrium and Disequilibrium, Resource Allocation, Introduction to Welfare Economics, Theory of the Firm, Introducing the Public Sector, Public Goods and Externalities, Environmental Economics, Financing the Public Sector, Issues of Public Policy, The Determination of Wages, Rewards to Factors of Production, Introducing Macroeconomics, National Income and Employment, Consumption and Investment, Money, Money and National Income, Cyclical Fluctuations, Economic Growth and Development, Macroeconomic Policies, Unemployment, Inflation, The Balance of Payments and Exchange Rates, International Trade and Policy, The European Community, Economic Inequality, Selected Economists, Questions and Answers, Index.